(untitled) (Asian Journal of Medical and Biological Research, 2021)
The aim of the study was to compare the efficiency of organic matter degradation between composting and vermicomposting as well as the possibility of making compost and vermicompost using cattle manure. The experiment was conducted with two treatments, where one was conventional composting (T1) and another was vermicomposting (T2) from cattle manure. The sample from composted materials was collected at 0, 20, 40 and 60th day of experiment. Parameter studied were dry matter (DM), crude fiber (CF), crude protein (CP), ether extract (EE), ash content of the samples as well as pH and temperature change during the experimental period. Results found that a significant higher DM (P<0.01) was found in T1 compared to T2. The CF degradation rate was significantly higher (P<0.01) in T2 compared to T1 group. The CP content also found significantly higher (P<0.05) in T2 compared to T1 group. There were no significant differences in EE and ash content as well as pH between the treatment groups. A typical temperature curve was found in T1 during active composting phase but the temperature was more or less same in T2 during the whole experimental period. From the experiment, it was found that crude fiber degradation rate is faster and CP content was higher in the T2 compared to T1 that might be indicated that vermicomposting is more beneficial than composting. Asian J. Med. Biol. Res. December 2020, 6(4): 768-776